Regulation of The Analysis of Suspicious Financial Transactions as Documentary Evidence - Ade Putra R; Yuliati Yuliati; Yenny Etta Widyanti; Milda Istiqomah (State Islamic University of North Sumatra Indonesia, 2025)
The handling of money laundering cases in Indonesia reveals a normative tension between evidentiary rules and the confidentiality regime governing financial intelligence. Financial Transaction Analysis Reports issued by the Indonesian Financial Transaction Reports and Analysis Center (PPATK) contain strategic information essential for tracing illicit financial flows, yet their evidentiary status remains contested due to statutory obligations to protect the identity of reporting parties. This study examines the legal position of financial intelligence reports within the Indonesian criminal justice system, particularly in relation to documentary evidence recognized under money laundering legislation. Employing a normative juridical method with statutory and conceptual approaches, the research analyzes relevant laws, judicial practices, and doctrinal interpretations governing evidence in money laundering prosecutions. The findings demonstrate that while money laundering laws formally recognize documents as valid evidence, financial intelligence reports are functionally constrained by confidentiality provisions, limiting their direct use in evidentiary proceedings. This legal ambiguity generates uncertainty in law enforcement practices and raises concerns regarding procedural fairness and legal certainty. The study concludes that a clearer regulatory framework is required to reconcile evidentiary needs with confidentiality obligations, ensuring both effective prosecution and protection of reporting entities.